ПІДПРИЄМСТВА ВОДОПОСТАЧАННЯ ТА ВОДОВІДВЕДЕННЯ В СВІТЛІ ТЕОРІЇ ПРИРОДНИХ МОНОПОЛІЙ: ПОЛІТЕКОНОМІЧНИЙ ТА ФІНАНСОВИЙ АСПЕКТИ (Світ фінансів, 2017)
Квасовський О. Р., Перевознюк В. В. Підприємства водопостачання та водовідведення в світлі теорії природних монополій: політекономічний та фінансовий аспекти. Kvasovskyy O., Perevozniuk V. Water supply and sanitation enterprises in national monopolies theory: economic andfinancial aspects. Conceptual basis of appearance and functioning of water supply and sanitation enterprises are developed through the prism of the natural monopolies theory. The additional problems are discovered that prevent the development of competition in this brunch, promising introduction of concession relations as an effective way of stimulation competition and modernization are proved.